Analysis of the Effects of Profitability Ratio and Macroeconomic Variables on the Stock Prices of Banking Companies Listed on the Indonesia Stock Exchange for the 2016-2023 Period - Pratama, Alfito Dias; Indraswari, Citra (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
This study aims to analyze the effects of profitability variables and macroeconomic variables on stock prices in banking sector companies listed on the Indonesia Stock Exchange for the period 2016-2023. The data used is secondary data with the panel data regression analysis method. The results indicate that ROA has a positive impact on stock prices, NIM has a positive impact on stock prices, inflation has a negative impact on stock prices, and interest rates have a negative impact on stock prices in banking sector companies. While ROE has no effect on stock prices in banking sub-sector companies.